Obesity prevalence in Gaziantep, Turkey - Ozcirpici Birgul; Coskun Ferhat; Sahinoz Saime; Ozgur Servet; Bozkurt Ali (Wolters Kluwer Medknow Publications, 2009)
Background: Obesity is associated with reduced quality of life, development of serious chronic conditions such as heart disease and diabetes, increased medical care costs, and premature death. Environmental effects, especially feeding habits may cause hyperinsulinemia and obesity. A Healthy People 2010 objective is to reduce the proportion of adults who are obese to 15%. Materials and Methods: This cross-sectional study was conducted on 1647 persons in a sample representing Gaziantep, Turkey. Over the selected 329 houses, 310 houses were reached (94.2%) and data about 1315 related persons was collected. The body mass index (BMI) shows the relationship between the weight and the height of people, calculated by the ratio of mass by kg over the square value of height measure. In statistical analyses chi-square, student′s t -test and logistic regression analysis were used. Results: The mean BMI increased with time for both sex, whereas decreased for 60+ age group. The fastest increase for both sex was seen while transition from 18 year to 19-29 age groups occurred. Another increase in women was in 30-39 age group; BMI=25.08±4.39 in 19-29 ages whilst BMI=29.02±5.79 in 30-39 ages. The increases in both sex in other age groups were not as much as in this group. Conclusion: Obesity is not only a problem in the Gaziantep but is also a major health concern in Europe and other regions of the world. As an accepted method against obesity, life-style changes should be put into use from childhood supported in school and family life.